ANALISIS EMOSI TOKOH UTAMA DALAM NOVAL HELLO KARYA TERE LIYE - Tamara, Tasya; Seli, Sesilia; Wartiningsih, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
This research aims to describe the influence of positive and negative emotions on the main character"™s attitude and the implementation of this research in Indonesian language learning at school. The benefits of this research are divided into theoretical and practical benefits. The theory used in this research is B.F. Skinner's theory. This research used descriptive qualitative method and used behavioural psychology approach. The data source in this research is the novel Hello by Tere Liye with data in the form of quotes, phrases, sentences, and paragraphs. The data collection technique used documentary study technique. The data collection tool for this research is the researcher herself as the primary instrument. The results indicate that: (1) Positive emotions including joy, love, admiration, and pleasure affect the main character's attitude. (2) Negative emotions including anger, hate, sadness, fear, and anxiety affect the main character's attitude. (3) The novel Hello by Tere Liye can be used as a teaching module for Indonesian language subjects and as a learning material to achieve learning objectives in class XII SMA.